Technological Attribution to Spoken English Language Learning Through Massively Multiplayer Online Role-Play Gaming (MMORPG) - Balqis Adris, Nadia; Yamat, Hamidah (International Journal of Engineering and Technology, 2018)
This paper presents and discusses a part of a study on the use of Massively Multiplayer Online Role-Play Gaming (MMORPG). The aim is to illuminate how the MMORP gaming technology helps learners in developing their spoken English competency. This ethnographic case study involved purposively selected participants - Zamurai and Cynthia. They were virtually observed through participant observation for 12 months as they developed from novices to expert players. Their chat and interview logs were triangulated for validity. Findings revealed an increase of more than 70% of online interaction while online conversations indicate increasing confidence, assertiveness, and deeper, more elaborative thoughts. The participants also felt that the: anonymous nature of online communication provided less threatening environment for social and language experimentation, time gaps in online chats turn-taking presented windows of language processing for comprehension, collaborative nature of the gameplay design provided exposure to spoken language models and feedback, and the semantically-mediated context-based authentic conversation provided a rich environment for language and cultural appropriation. These indicate the technological attributions of MMORPG in developing the skills needed for spoken language competency. It implies the need for a technological based approach in language teaching and learning and the potential of e-global language learning.Â Â